Disability policies and politics: A new perspective for Brazilian disability citizenship? - Kirakosyan, Lyusyena (Critical Disability Discourses, 2012)
Public policies aimed at assisting disabled citizens are a fairly recent development in Brazil. Prior to the advent of the nation’s relatively new rights-based policies, the politics of “assistencialism”— policies aimed at addressing the symptoms and not the causes of social ills—served as a rationale for such support as was provided to the nation’s disabled population. Civil society organizations have been fundamental in Brazil to advance the rights of disabled people. This article argues that civil society organizations and the state must act vigorously and jointly if assistencialism ultimately is to be overcome and full citizenship for disabled Brazilians is to be attained. The analysis is organized into three parts. First, it briefly describes the evolution of the struggle for rights for disabled Brazilians during the past three decades. Second, the article examines the government’s recent rights-based policies and advocacy organizations’ claims. The article concludes by offering a brief analysis of how the contemporary policy initiatives have contributed to the development of Brazilian citizenship and democracy. Keywords: disability policy, democracy, civil society, citizenship, Brazil.